Academic Stress Factors Among Indonesian Students: A Case of IAIN Batusangkar - Munir, Sirajul; Anita, Rini; Sefnimal, Tessa Dwi Okmala (Jurnal Pendidikan Progresif, 2020)
Academic Stress Factors Among Indonesia Students: A Case of IAIN Batusangkar. Objective: This present study aims at investigating factors causing students’ academic stress among Indonesian students Methods: This research used cross-sectional design. The data analysis used descriptive statistics with statistical analysis tool, SPSS 22. Findings: This study indicates that the causes of academic stress are different at each semester of students. Family causal factor, for example are the most factors affect the second semester. Likewise, family causal factors, academic causal factors, personal causal factors, and peer pressure are factors faced by the fourth and sixth semester students. Peer pressure, however, is experienced for the eighth semester students. Conclusion: These findings conclude that students are vary in the causes of academic stress.Keywords: academic stress, academic achievement, students’ academics stress DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202004